2020
DOI: 10.1111/ele.13445
|View full text |Cite
|
Sign up to set email alerts
|

A chemically triggered transition from conflict to cooperation in burying beetles

Abstract: Although interspecific competition has long been recognised as a major driver of trait divergence and adaptive evolution, relatively little effort has focused on how it influences the evolution of intraspecific cooperation. Here we identify the mechanism by which the perceived pressure of interspecific competition influences the transition from intraspecific conflict to cooperation in a facultative cooperatively breeding species, the Asian burying beetle Nicrophorus nepalensis. We not only found that beetles a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…A pair of beetles works together to convert the carcass into an edible carrion nest for their larvae by removing any fur or feathers, and rolling the meat into a ball. The beetles also reduce competition with rival species for the resources on the dead body by smearing the flesh in antimicrobial exudates, consuming eggs laid by rival insects and concealing the body below ground ( Chen et al, 2020 ; Duarte et al, 2018 ; Scott, 1998 ). During carcass preparation, beetle eggs are laid in the surrounding soil and then hatch within 3–4 days.…”
Section: Introductionmentioning
confidence: 99%
“…A pair of beetles works together to convert the carcass into an edible carrion nest for their larvae by removing any fur or feathers, and rolling the meat into a ball. The beetles also reduce competition with rival species for the resources on the dead body by smearing the flesh in antimicrobial exudates, consuming eggs laid by rival insects and concealing the body below ground ( Chen et al, 2020 ; Duarte et al, 2018 ; Scott, 1998 ). During carcass preparation, beetle eggs are laid in the surrounding soil and then hatch within 3–4 days.…”
Section: Introductionmentioning
confidence: 99%
“…Since carcass preparation and burial, which occur above ground, are critical to the successful breeding of burying beetles, we believe that air temperature is an appropriate measure of environmental temperature (see also refs. 32,60,61 ). Although we acknowledge that soil temperature could be important for the larva development, those data are not available.…”
Section: Methodsmentioning
confidence: 99%
“…A 2 × 2 cm iron mesh was placed around the top of the large container’s wall to let flies access the carcass but to keep out larger animals that might scavenge the carcass. Small, non-cooperative groups contained one male and one female, whereas large, cooperative groups contained three males and three females ( Chen et al, 2020 ; Liu et al, 2020 ). We captured the local beetles using the same hanging pitfall traps described above, and then conducted two group size treatments at each site.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to interspecific competition, intraspecific cooperative behavior among beetles may also modulate their realized TPC. Previous studies have shown that cooperative carcass preparation and burial enables beetles to outcompete blowflies and expand their thermal niche to warmer environments ( Sun et al, 2014 ; Chan et al, 2019 ; Chen et al, 2020 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%